Prospects for multilateralism at the end of the liberal order - Ng, Joel (2025)
The US withdrawal of support for multilateral organisations is impending, and short-term disruption is inevitable. However, the long-term solutions that generate international order will prevail if other states are bold in their thinking and persist in cooperation.